Covid-19 Epidemiology in Madura: Public Behaviors’ Compliance to Goverment Policy - Firdaus, Thoriqi; Nisak, Khoirun; Putri, Mita Oktavia; Shodiq, Muhammad Ahsan Fatwaddin (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: A new variant of SARS-CoV-2 has emerged, namely Omicron variant virus. This variant has a fast transmission power and even affects the vaccine's effectiveness. Disobedience to the government regulations resulted in the spread of the viruses. One of the efforts to provide knowledge to the public is an effective communication through various media and methods. This research intends to analyze Madura society behavior on Indonesian government policies in this COVID-19 pandemic of Omicron variant.Methods: This study used a mixed-method with a cross-sectional study design. The study population were the all people who live in Madura, while the subjects of this study was 80 people. The quantitative data analysis was conducted using SPSS 20 software. The qualitative data  collection was done through observations and interviews.Results: Omicron variant of COVID-19 infects all ages in Madura. Among all of the subjects, 51.2 % infections were caused by disobeying the health protocols. Among the disobeys, 66.3 % did not use mask. The infection spread from their own region occurred on 58.8% of the subjects. The most often symptom was sore throat without any cough (71.3%). Among the subjects, 71.25% did not care about Omicron variant of COVID-19, 71.25% people lose their trust to vaccine and governments, 53.75% people did not care about the government policy.Conclusion: The spread of Omicron variant virus in Madura associated to the behavior of the subjects who had low concerns about COVID-19 epidemic. The loss of public trust in vaccines and the government relate to the compliance to the health protocols.